Investigative didactic-methodological work coordinating socio-medical inter-subjects. - Marta Luján Hernández; Sara Hernández Malpica; Mirtha A. Hernández López; Lino Ortiz Santiesteban; Irma Pasarón Pérez; Pedro Hernández Sánchez (Medisur)
A qualitative action-investigation of the pedagogical profile was performed. It was based on the research, methodological, and didactic work of inter subjects coordiantions of the socio-medical subject matter of the Medicine carrer. It was developed by several meetings of table work that permitted the review of the curriculums and the current objectives of the following subjects; Introduction, to General and Integral Medicine, Phylosophy and Health, Sanología, Public Health, and General and Integral Medicine II. Documentary observation was carried out by means of the analysis of the content technique of different programs. Proper correcteness were preformed to avoid recurrence or omission of similar contents in 4th and 5th year of medicine specialty. It was determined ";what to teach and how to do it";, not only for the management of different invariants but also in what is important to be mastered in the future General Comprenhensive Doctor. After the comparison of the differente curriculums, a proposal was elaborated to be taken to the Comite Vertical y Horizontal (staff meetings of an academic year of different specialties) to be put into practice in the academic year 2004-2005.